Vaccinating to Prevent Antibiotic Use: Potential Impact of a Group A Streptococcus Vaccine on Acute Respiratory Infections. (October 2020) - Lewnard, Joseph; King, Laura; Fleming-Dutra, Katherine; Link-Gelles, Ruth; Beneden, Chris Van
Abstract : Background: Group A Streptococcus (GAS) causes acute upper respiratory tract infections that are frequently treated with antibiotics. GAS vaccines in development may prevent both disease and outpatient antibiotic prescribing. We estimated (1) the incidences of GAS-attributable pharyngitis, sinusitis, and acute otitis media (AOM) infections in the United States; (2) the proportion of these infections resulting in antibiotic prescriptions; and (3) the incidence of infection and antibiotic prescribing potentially preventable by vaccination against GAS. Methods: We estimated annual rates of US outpatient visits and antibiotic prescriptions for pharyngitis, sinusitis, and AOM using physician office and emergency department visit data in the National Ambulatory Care Survey and National Hospital Ambulatory Medical Care Survey from 2012 to 2015. We supplemented this with visits to other outpatient settings (eg, urgent care) from the 2016 IBM MarketScan Commercial Database. We estimated the proportion of episodes attributable to GAS and to GAS emm types targeted by a 30-valent vaccine in development using data from previously conducted etiology studies. We estimated the incidence of disease and antibiotic prescribing preventable by a vaccine meeting the WHO 80% efficacy target for preventing noninvasive GAS disease, with doses administered during infancy and at age 4 years. We estimated the proportion of outpatient antibiotic prescribing preventable by vaccination by dividing estimates by total antibiotic dispensations, estimated from the IQVIA TM dataset. Results: Among individuals aged 0–64 years, GAS causes 27.3 (95% CI, 24.6–30.6) ambulatory care visits and 16.4 (95% CI, 14.5–18.6) outpatient antibiotic prescriptions per 1, 000 population annually for pharyngitis, sinusitis, and AOM combined, representing 2.1% (95% CI, 1.8%–2.4%) of all outpatient antibiotic prescriptions. Among children aged 3–9 years, GAS-attributable incidence includes 124.4 (95% CI, 109.0–142.1) visits and 77.1 (95% CI, 65.7–90.6) antibiotic prescriptions per 1, 000 population annually, representing 8.6% (95% CI, 7.3%–10.1%) of antibiotic prescriptions in this age group. Individual-level direct protection from a 30-valent vaccine meeting the WHO target could prevent 26.0% (95% CI, 24.0%–28.1%) of pharyngitis visits; 17.3% (95% CI, 15.5%–19.5%) of pharyngitis, sinusitis, and AOM visits; and 5.5% (95% CI, 4.7%–6.4%) of outpatient antibiotic prescriptions among children aged 3–9 years. If vaccination eliminated the need for antibiotic treatment of pharyngitis (for which GAS is the only etiology warranting antibiotic treatment), the total effects of vaccination could include the prevention of up to 17.2% (95% CI, 15.0%–19.6%) and 6.8% (95% CI, 6.3%–7.3%) of antibiotic prescriptions among persons 3–9 years and 0–64 years of age, respectively. Conclusions: In addition to preventing infections and healthcare visits, an efficacious GAS vaccine could prevent a substantial volume of outpatient antibiotic prescribing in the United States. Funding: This work was supported by the Centers for Disease Control and Prevention. The findings and conclusions in this report are those of the authors and do not necessarily represent the official position of the Centers for Disease Control and Prevention. Disclosures: Laura M. King is a contractor employed by Northrop Grumman Corporation to fulfill research needs at the Centers for Disease Control and Prevention as part of a contract covering many positions and tasks. All other authors declare no conflicts.